The Effect of Angiotensin Converting Enzyme Inhibitor Therapy on Publication Rates and Characteristics of Abstracts Presented in The First National Pediatric Orthopedics Congress: A Bibliometric Study - (:unkn) unknown (My University, 2020)
INTRODUCTION: Publication rates, number of citations, and quality of journals publishing presentations in a congress are considered among important factors which defines the value of the congress. The purpose of this study is to evaluate publication rates and characteristics of oral and poster presentations of the first National Pediatric Orthopedics Congress in Turkey.METHODS: We reached abstracts of oral and poster presentations of first National Pediatric Orthopedics Congress through the official web site of the Pediatric Orthopedic Society. Presentations were searched via scientific databases using author names. Studies; were evaluated in the context of the journal, time between congress and publishing, impact factor, Scimago point, and index of journal, number of citations, and first authors institution.RESULTS: Between congress and time of this study, 36,7% of presented papers were published. Journals published oral presentations had an average impact factor of 1,524 (0,39-4,154) and Scimago point of 0,75 (0,265-1,57) at the time of the study. These values were for poster presentations; 1,051 (0,39-2,383) and 0,663 (0,355-1,129) respectively. Oral and poster presentations were published an average of 20,9 and 23,75 months after congress respectively. At the end of the four years, the number of citations of oral presentations were 0-25 and poster presentations 0-8. Affiliation of first authors of papers were 32 university hospital, 18 research hospital, 6 general state hospital, 5 private hospitals.DISCUSSION AND CONCLUSION: A high percentage of orally presented papers and also posters progressed to original articles. Although the time from the presentation to publication was somewhat long, they appeared in high-quality journals.

GİRİŞ ve AMAÇ: Bir kongrede sunulan bildirilerin yayına dönüşme oranları, aldıkları atıf sayıları ve yayınlandıkları dergilerin kaliteleri, kongrenin değerini belirleyen faktörler arasında kabul edilirler. Bu çalışmanın amacı; 1. Ulusal Çocuk Ortopedisi Kongresi’nde sunulan sözel ve poster bildirilerin yayına dönüşme oran ve özelliklerini değerlendirmektir. YÖNTEM ve GEREÇLER: Birinci Ulusal Çocuk Ortopedisi Kongresi bildiri özetlerine Çocuk Ortopedisi Derneğinin resmi internet sitesinden ulaşıldı. Yazar isimleri kullanılarak yayınlar bilimsel arama motorları üzerinden tarandı. Çalışmalar; dergi, kongre ile yayın olmaya kadar geçen süre, dergilerin etki faktörü ve Scimago puanı, kayıtlı oldukları indeks, atıf sayısı ve ilk yazarın bağlı oldukları kurum özellikleri açısından değerledirildi. BULGULAR: Kongre ile çalışma arası sürede bildirilerin %36,7'si yayına dönüşmüştü. Sözlü bildirileri yayınlayan dergilerin etki faktörü 1,524 (0,39-4,154) ve Scimago puanı 0,75 (0,265-1,57) iken bu değerler poster sunumlar için sırası ile 1,051 (0,39-2,383) ve 0,663 (0,355-1,129) olarak hesaplandı. Sözel bildirler kongre sonrası ortalama 20,9 ayda yayınlanırken, poster bildiriler için bu süre 23,75 aydı. Dört yıllık sürenin sonunda sözel bildiriler 0-25, poster bildiriler 0-8 atıf almışlardı. İlk yazarların bağlı olduğu kurumlar; 32 üniversite hastanesi, 18 eğitim araştırma hastanesi, 6 devlet hastanesi ve 5 özel hastane şeklindeydi. TARTIŞMA ve SONUÇ: Birinci Ulusal Çocuk Ortopedisi kongresinde sunulan sözel bildirilerde daha fazla olmak üzere yüksek oranda yayına dönüşmüşlerdir. Kongre ile ile yayına dönüşme arası süre biraz uzun olsa dahi, yüksek kalitede dergilerde yayınlanmışlardır.
1. Ulusal Çocuk Ortopedisi Kongresi’nde Sunulan Bildirilerin Yayına Dönüşme Oranı ve Özellikleri: Bibliyometrik Analiz